2022
DOI: 10.3389/fgene.2022.918977
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer analysis reveals the genetic alterations and immunotherapy of Piezo2 in human cancer

Abstract: Background: Piezo2 is a transmembrane-spanning ion channel protein implicated in multiple physiological processes, including cell proliferation and angiogenesis in many cell types. However, Piezo2 was recognized as representing a double-edged sword in terms of tumor growth. The prognostic and immunotherapeutic roles of Piezo2 in pan-cancer have not been reported.Methods: In this study, several databases available including the UCSC Xena database, HPA, TIDE, GSEA, and cBioportal were used to investigate the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Limited research has been conducted on their functions in immune cells and their associations with disease. A pan-cancer analysis revealed that Piezo2 is associated with T-cell dysfunction and the secretion of immune-related factors, with the precise mechanism requiring further clarification [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limited research has been conducted on their functions in immune cells and their associations with disease. A pan-cancer analysis revealed that Piezo2 is associated with T-cell dysfunction and the secretion of immune-related factors, with the precise mechanism requiring further clarification [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Last year, an extensive in silico analysis of Piezo2 expression, genetic relationships with immunological markers, and predictive functions in pan-cancer was performed. This study indicated that Piezo2 expression is cell- and tissue-dependent in different cancer types and is related to prognosis in several tumors [ 132 ].…”
Section: Mechanoreceptors In Cancermentioning
confidence: 99%
“…Moreover, the 5-year survival rate of patients with advanced lung carcinoma has increased to 16% (5). The PACIFIC study suggested that immune maintenance therapy after radical concurrent chemoradiotherapy for stage III inoperable locally advanced NSCLC can significantly improve the survival of patients, and it has become the standard treatment recommended by the guidelines (6). Also, the application of immune checkpoint inhibitors can achieve sustained and effective remission in lung cancer, melanoma, bladder urothelial carcinoma, and Hodgkin's lymphoma (7), and patients can survive for a long time.…”
Section: Introductionmentioning
confidence: 99%